Intensity of light impurities separation in vertically ascending air flow - V. G. Khamuev (Сельскохозяйственные машины и технологии)
In channels of pneumoseparators with vertical giving of an air flow process of separation of an easy component is casual because of a wrong form of caryopsis and irregularity in the distribution of an air stream on the cross section of the channel. Therefore the separated component can not be completely allocated for any final time of influence of an air flow. It is confirmed by the mathematical model which is adequately described by function of gamma distribution with arguments one of which is the important parameter of intensity of easy component separation. Just as the movement of a material point is determinet by its speed in each timepoint, and process of pneumoseparation is characterized on intensity of extraction of an easy component. The authors showed that this parameter makes the physical meaning opening possibility of an intensification of process of pneumoseparation that was not investigated adequately. Influence of grain charge on intensity of process of separation in vertically ascending air flow was studied. It is established that the increase in specific grain charge in the pneumoseparating channel with vertically ascending air flow is followed by increase of intensity of light impurities separation that can be explained by increase of speed of an air stream in intergrain space. When processing of barley at specific grain charge from 0.5 to 2 kg on sq. cm an hour intensity of impurity (oats) release increases depending on loading linearly. If intensity of process of separation at increase in loading from 0.5 to 2 kg on sq. cm per hour remained same as at charge of 0.5 kg of sq. cm per hour, settlement separation of oats at charge of 2 kg of sq. cm per hour would decrease from 51.97 percent (result of experience) to 9.83 percent. So, efficiency of separation with use of the pneumoseparating channel depend on change of grain charge.